Колдовской Мир: Романы / А. Нортон; пер. С. Степанов, А. Пахомов - Нортон Андре (Северо-Запад, 1992)
8-11 кл Экземпляры: Нефтебазинская библиотека (20070809) / Инвентарный номер: 34164z2 / Авт.знак: Н 83 / ББК: 84(7Сое)